Proposal for an Energy Efficiency Index for Green Hydrogen Production—An Integrated Approach - Luciano T. Barbosa; Pedro A. C. Rosas; José F. C. Castro; Samuel D. Vasconcelos; Paulo H. R. P. Gama; Douglas C. P. Barbosa (Energies, 2025)
In the context of mounting concerns over carbon emissions and the need to accelerate the energy transition, green hydrogen has emerged as a strategic solution for decarbonizing hard-to-abate sectors. This paper introduces a methodological innovation by proposing the Green Hydrogen Efficiency Index (GHEI), a unified and quantitative framework that integrates multiple stages of the hydrogen value chain into a single comparative metric. The index encompasses six core criteria: electricity source, water treatment, electrolysis efficiency, compression, end-use conversion, and associated greenhouse gas emissions. Each are normalized and weighted to reflect different performance priorities. Two weighting profiles are adopted: a first profile, which assigns equal importance to all criteria, referred to as the balanced profile, and a second profile, derived using the analytic hierarchy process (AHP) based on structured expert judgment, named the AHP profile. The methodology was developed through a systematic literature review and was applied to four representative case studies sourced from the academic literature, covering diverse configurations and geographies. The results demonstrate the GHEI’s capacity to distinguish the energy performance of different green hydrogen routes and support strategic decisions related to technology selection, site planning, and logistics optimization. The results highlight the potential of the index to contribute to more sustainable hydrogen value chains and advance decarbonization goals by identifying pathways that minimize energy losses and maximize system efficiency.